Can the attitude of implementing an occupational safety and health program improve employee work discipline? - Saputra, Trio; Junaidi; Fajarwaty Kusumawardhani; Abdul Mirad; Irawati (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
This research aims to determine the relationship between attitudes towards implementing occupational safety and health programs and employee work discipline. This research used as subjects 57 employees of PT. PLN (Persero) Pekanbaru branch, research data was collected using two scales, namely the attitude scale for implementing occupational safety and health programs compiled by the researcher himself with a total of 30 items and the employee work discipline scale used was compiled by the researcher himself based on disciplinary theory with a total of 28 items. Sampling in this research used the summated ratings method, data analysis using product moment analysis, with the help of the SPSS 24.0 for Windows computer program. Based on the results of the analysis, it was found that there was a positive relationship between the attitude towards implementing occupational safety and health programs and employee work discipline, the correlation coefficient was 0.738 with p = 0.000, so the hypothesis was accepted, meaning that the higher the attitude towards implementing occupational safety and health programs, the greater the contribution to improve employee work discipline